Mentoring Kader Terhadap Pencegahan Stunting Di Desa Sari Mulyo Kecamatan Sukaraja - Herlinda Herlinda; Iin Nilawati; Novi Lasmada Sari; Erli Zainal; Parwito Parwito (Bengkulu Institute, 2023)
Stunting is one of the crucial health problems in Indonesia and is the focus of attention. The prevalence of stunting from year to year tends to fluctuate from 35.6% in 2007 to 37.2% in 2013, and decreased to 27.7% in 2019. Despite the decline, in Indonesia the disparity is quite wide between provinces and regions. The average decline is still slow, while the target in 2024 is to reduce the stunting rate to 14% and in Bengkulu Province the stunting rate is still quite high. Stunting has an impact on the development of the quality of human resources. Based on this, the long-term goal of this service is to participate in reducing stunting through preventive / prevention efforts, with this mentoring can provide knowledge about stunting prevention strategies with Spider Risk. The method of implementing cadre mentoring with the principle of community empowerment begins with a field survey and carrying out an advocacy role. The form of community empowerment is carried out in collaboration with cadres. After participating in mentoring for approximately one month, cadres understand stunting prevention efforts, namely by conducting prevention planning, targeting starting from pre-conception catin, implementation, counseling and counseling, mentoring starting from catin, pregnant women, giving birth to 1000 HPK, on a scheduled and continuous basis, monitoring and evaluating the success of the strategy. Cadres understand stunting prevention strategies and are confident in assisting families at risk of stunting. Cadres prefer to use manual documentation using books.